Evaluation of waist circumference to predict general obesity and arterial hypertension in women in Greater Metropolitan Belo Horizonte, Brazil - Gustavo Velásquez-Meléndez; Gilberto Kac; Joaquim Gonçalves Valente; Roberta Tavares; Cibele Queiroz da Silva; Emerson Silami Garcia
This study examined the capacity of waist circumference (WC) to identify subjects with overweight (BMI ³25) and obesity (BMI ³30), in agreement with internationally recommended levels of action. Data were obtained from 791 women, 15-59 years old. After identifying overweight and obesity according to WC values, sensitivity and specificity were calculated to verify whether WC could be a good risk predictor for hypertension. Associations were tested by linear regression and logistic regression, controlling for confounding. WC cut-off points of 80cm and 88cm correctly identified 89.8% and 88.5% of women with overweight and obesity, respectively. Abdominal obesity (WC ³88cm) was statistically associated with hypertension in the multivariate analysis (OR = 2.88; 95% CI: 1.77-4.67). Hypertension was identified with a sensitivity of 63.8% and 42.8%, and with a specificity of 68.0% and 83.3%, for WC ³80 and ³88, respectively. The proposed cut-off points for abdominal obesity can potentially distinguish individuals at risk for future obesity, but has only moderate power to predict individuals with high blood pressure.